The Role Of Parents In Meeting The Basic Physical Needs (Love, Nurture, Hone) Of Children With Down Syndrome In Tunge Village - Dodik Arso Wibowo; Wahyu Tanoto (Chakra Brahmanda Lentera Institute, 2022)
Background: Down syndrome is the retardation of physical and mental growth caused by the developmental abnormalities of chromosome 21 that impact physical and mental barriers that experience the barriers of intellectual development and difficulty in adapting to the environment in everyday life. Children with Down syndrome have distinctive acceptable motor characteristics and other characteristics based on the degree of obstacles it has, which are coarse-hand fingers, stiff, weak muscles, emotional conditions that are difficult to guess and poorly restrained, dependence on adults, and often reject others. The research aims to know the parents' role in fulfilling the basic needs of physical (love, nurture, hone) of children with Down syndrome in Tunge village. Methods: The design of this study uses descriptive, a research population of 16 respondents, and a large sample of 16 respondents with the technique of